2013
DOI: 10.1096/fj.13-238600
|View full text |Cite
|
Sign up to set email alerts
|

Influence of proinflammatory stimuli on the expression of vascular ribonuclease 1 in endothelial cells

Abstract: Extracellular RNA (eRNA) released under injury or pathological conditions has been identified as a yet unrecognized vascular alarm signal to induce procoagulant, permeability-promoting, and proinflammatory activities. eRNA-induced functions were largely prevented by administration of RNase1 as a natural blood vessel-protective antagonist of eRNA. The aim of this study was to investigate the inflammatory regulation of endothelial cell RNase1, which is partly stored in Weibel-Palade bodies of these cells. Long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(52 citation statements)
references
References 29 publications
(41 reference statements)
1
50
1
Order By: Relevance
“…Similarly, Gansler et al [18] found that TNFα decreases RNase1 production by human umbilical vein endothelial cells. In contrast, Etoh et al [54] found that TNFα induced RNase5 mRNA expression in human colon cancer cells.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Similarly, Gansler et al [18] found that TNFα decreases RNase1 production by human umbilical vein endothelial cells. In contrast, Etoh et al [54] found that TNFα induced RNase5 mRNA expression in human colon cancer cells.…”
Section: Discussionmentioning
confidence: 88%
“…For example, tumor necrosis factor-α (TNFα) decreases RNase1 production by human umbilical vein endothelial cells [18]. Although TNFα inhibits basal and FSH-induced steroidogenesis in granulosa cells (GC) and is thought to play a role in the regulation of ovarian function [19, 20], the effect of TNFα on ovarian BRB production is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Concurrently, the intrinsic RNase activity was increased following MI, possibly as a direct response to the release of eRNA following myocardial injury or via eRNA‐induced inflammatory stimuli,22 as eRNA has been reported to induce RNase release from endothelial cells in vitro following inflammatory stimulation. The eRNA was measured in platelet‐free plasma and may be released by different sources including necrotic cells, apoptotic cells, or activated platelets at the sites of injury.…”
Section: Discussionmentioning
confidence: 98%
“…19 Long-term treatment (for several hours) of endothelial cells with proinflammatory cytokines, such as TNF-α or IL-1β, results in significant downregulation of RNase1-mRNA and RNase1-protein levels, mainly involving epigenetic regulation of histone modifications. 96 This indicates that acute inflammatory conditions promote a temporary RNase1 release to degrade the excess of proinflammatory eRNA, whereas chronic stimulatory conditions lead to a decreased RNase1 production, thereby providing another regulatory aspect of the vascular eRNA/RNase system. In which way extracellular miRNAs are affected by changes in circulating RNase1 concentrations remains to be analyzed.…”
Section: Ernases As Natural Counterparts Of Extracellular Nucleic Acidsmentioning
confidence: 99%
“…19,96,97 Also after acute myocardial infarction, serum RNase activity was described to increase at 1 day, peaking at 3 to 5 days and returning to baseline at 14 weeks after injury, compared with healthy controls. 98 In experimental atherosclerosis in Ldlr −/− mice, a biphasic characteristic of RNase activity was observed with a temporary increase during the first 2 weeks, followed by a significant and sustained decrease to ≈20% to 40% of the activity in baseline controls, starting at 4 weeks of HFD feeding throughout the 36 weeks of the observation period.…”
Section: Ernases As Natural Counterparts Of Extracellular Nucleic Acidsmentioning
confidence: 99%